The effect of paying parents to adopt: Evidence from Minnesota's foster-care system - Kelly C. Bishop; Diana E. Mac Donald (Banco de México, 2022)
Aimed at increasing the adoption rate of older children, Minnesota's 2015 Northstar Care Program eliminated the adoption penalty (the decrease in fostering-based financial transfers associated with adoption) for children aged six and older, while maintaining it for children under age six. Using a difference-in-differences estimation strategy that controls for a rich set of covariates, we find that parents responded positively to this change in direct financial payments; the annual adoption rate of older foster children aged six to eleven increased by approximately 7 percentage points (22% at the mean) as a result of the program. We additionally find evidence of strategic adoption behavior as the adoption rate of younger children temporarily increased by 11 percentage points (26% at the mean) in the year prior to the program's implementation.
Keywords: D1; J13; I38; H75; 330; Family Policy; Government Transfers; Adoption; Foster Care